Silent Internationalization at the State Distance University of Costa Rica: Characteristics and behavior over time of university students according to their country of origin (Praxis Educativa, 2026)
This study aims to provide a detailed characterization of the student population at the Universidad Estatal a Distancia (UNED) whose country of origin is not Costa Rica, to better understand their main features, behavior over time, and permanence or temporality of this population within the institution, and the relevance of institutional support such as financial aid (scholarships). The study uses a panel data set extracted from UNED's Information System for Decision-Making Support and Institutional Management (SIATDGI), containing historical information on students, their enrollment behavior, demographic data, nationality, and detailed information on institutional support and academic performance. The sample comprises a total of 17,825 observations distributed across 4,017 unique student groups, from the first quarter of 2015 to the first quarter of 2024. To analyze the influence of financial aid on the number of credits enrolled by the selected student sample, fixed and random effects regression models were employed, along with cluster analysis to identify homogeneous groups within the student data, and ANOVA analysis to assess significant differences between the identified clusters. The results confirm a positive and significant effect of financial aid on the credit enrollment behavior of the study population. The study suggests that it is relevant for the institution to develop affirmative action policies for this population, similar to those already implemented by UNED for other groups, and the development of broader regional and global internationalization policies.
Keywords: Higher education internationalization; Distance education; international student; Migration; Internationalization for society